Subtitling Strategy And Accuracy Of Elements Within Direct Speech In Ice Age: Dawn Of Dinosaurs Movie - FARISI , ERSYAD AL (2012)
These purposes of this research are to describe the strategies of subtitling in ice age: Dawn of the Dinosaurs movie and to describe the accuracy of those elements within direct speech subtitling. The data are written expression consisting of expansion strategies and deletion strategies used in the subtitling result in ice age: Dawn of the Dinosaurs movie. In collecting of the data, the writer uses documentation method. The techniques for getting the data are watching the movie, listening to the utterances, reading the subtitling result, putting sign and making check list on the elements within direct speech sentence on subtitling result in the movie and gathering the data of element within direct speech sentence on subtitling result in the movie. The collected data are analyzed by using Nida's expansion and deletion strategies theory. The results of this research show that (1) the expansion strategies in subtitling are implemented by filling out elliptical expression obligatory specification, and doublets. The strategy which is mostly used in expansion strategies is doublets, the deletion strategies in subtitling are implemented by repetition, formulae, and categories The strategy which is mostly used in deletion strategies is formulae and (2) the accuracy of those direct speech in subtitling.